Exploring the prioritisation process of the sustainable development goals by business - Kaffashi, Sara; Grayson, David (World Association for Sustainable Development (WASD), 2021)
Purpose: This study aims to investigate the emergent working practice in terms of how individual businesses determine which SDGs are most relevant to them and therefore which ones to prioritise for practice. Design/methodology/approach: A questionnaire-based method was applied to enhance corporate sustainability experts’ opinion on the specific subject of the SDGs prioritisation process. Findings: The results of this study suggest that board and CEO involvement in the process of decision making for SDGs is lacking. Interestingly, the existence of current policies in place to reduce or subside negative impacts together with commercial reasons found to be the main motivation for prioritisation. Yet, many respondents indicated drawing a materiality matrix for the prioritisation process. Further investigations in data indicated a lack of active research, ambition, and more accurate reporting system on SDGs for many studied companies. Practical implications: The result implies the need for regulatory policies for a quantitative reporting scheme. This will document both negative and positive impacts that can be measured clearly with KPIs together with their financial implications. Another policy implication is for the government to introduce additional legislation and actively engage with industry to ensure that SDG goals that are agreed by the global international community are adequately mandated. Originality/value: This study adds to businesses' wealth of information on the SDG prioritisation steps by combining different variables that are significant determinants of the SDG selection process. It also provides an essential piece of information for businesses, sustainability leaders, policymakers, and broader society to consider about “who”, “why” and “how” the SDGs prioritisation decision are being made.
Keywords: Sustainable Development Goals; Prioritisation; Sustainability Management; SDG Selection Personnel; SDG Selection Methods; Materiality Matrix